The influence of studies in Cognitive Wellness University for the elderly people on maintaining their cognitive functions. - L. V. Usenko; G. S. Kanyuka; D. V. Oleniuk; O. O. Usenko; J. V. Silkina (Medičnì Perspektivi)
Progressive aging of the population is accompanied by age-related changes in the body, primarily from the central nervous system, which causes a decline in the cognitive health of man and society as a whole. The emergence of cognitive deficits leads to a decrease in a person's ability to think, learn, actively perceive information, make decisions, worsen other psycho-physiological functions.The aim of our study was to assess the state of cognitive functions of the elderly people, the dynamics of their changes, depending on the age stage of life, as well as under the influence of program exercises and specially designed trainings aimed at activating mental and physical activity. 165 students of the university aged 55-85 years took part in the study. Two groups of subjects were identified. The first one numbering 100 people we divided into 3 subgroups in order to identify phased age-related changes in cognitive functions and, depending on this definition, the need for preventive or corrective measures: 1 subgroup - 55-65 years, 2 subgroup - 66-75 years and 3 subgroup - 76 years and older. The study of their cognitive functions was determined upon admission to the university. The second group consisted of 65 people, whose indicators of cognitive functions were determined in dynamics: at admission to the university and at the completion of training. To assess the level of cognitive functions, we used a formalized screening technique - the Montreal Scale. The established dynamics of the components of cognitive functions, depending on age, makes it possible to differentially approach the choice of preventive or corrective measures aimed at activating cognitive functions, in each age group with an emphasis on those of them that have been changed to a greater extent. The effectiveness of the proposed structure of studies at the university for the elderly was shown.